The role of Nrf2 transcription factors in various physiological and pathological states - Deasyka Yastani; Sri Widia A Jusman (Acta Biochimica Indonesiana, 2023)
Since its first report in 1994, understanding of the nuclear factor erythroid 2-related factor 2 (Nrf2) has continued to grow. Initially recognized for its role in cellular response to oxidative stress, Nrf2 is now known to be involved in a variety of regulatory process, including metabolic regulation, autophagy, protein homeostasis (proteostasis), and mitochondrial biogenesis. The expression of Nrf2 target genes is highly dependent on stimulus activation and interactions with transcription factors, activators, and repressors. Nrf2 activation serves as a defense mechanism under physiological conditions, but in the context of cancer, it can trigger the development of cancer cells due to its complex roles. Nrf2 is strongly associated with the onset and development of many diseases, including those caused by metabolic disorders and inflammation. Understanding Nrf2's diverse functions offers valuable insights into disease pathogenesis and potential therapeutic approaches. This review explores the pleiotropic role of Nrf2 regulation.